Sequence matters! Retrieval practice before generative learning is more effective than the reverse order. (August 2022) - Roelle, Julian; Froese, Linda; Krebs, Rebecca; Obergassel, Niklas; Waldeyer, Julia
Abstract: As follow-up to an initial study phase, both generative learning activities and retrieval practice can substantially enhance learning, but via different functions. Generative activities are theorized to mainly serve the function of constructing coherent mental representations of the learning content that are well integrated with prior knowledge, whereas retrieval practice is theorized to mainly serve the function of consolidating learners' mental representations in memory. In view of these complementing functions, the present study investigated whether the sequence of these activities matters. In an experiment with N  = 158 university students, we varied the sequence of generative learning and retrieval practice after an initial study phase. We found that the retrieval-before-generation sequence yielded better retention and reduced cognitive load during both types of activities. We conclude that although it might seem counterintuitive, engaging learners in retrieval practice before engaging them in generative learning can be more beneficial than vice versa. Highlights: Retrieval practice before generative learning is more effective than vice versa. Engaging in retrieval practice first fosters retention. Engaging in retrieval practice first reduces subjective cognitive load. The retrieval-first effect on extraneous load mediates the effect on retention.